Insecticide phytocoil production from neem based materials and characterization of neem oil extract - Tahiru Saka; Aadil Khursheed; Abdulhalim Musa Abubakar; Gaurav Kumar Pandit; Peter Simon; Mamoudou Hamoudou (Institute of Computer Science (IOCS), 2023)
Neem based materials are abundant in almost every part of the world. It is allowed to litter the environment and eventually swept and disposed. In this study, neem oil was extracted from neem seeds kernel and its characterization was done by proximate analysis to determine the physico-chemical properties of the oil extracted. From the experiment, the moisture content, oil content, saponification (SAP) value, color and nature at room temperature of the grinded neem seed are 11.4%, 48.4%, 171 mg KOH, golden yellow and liquid, respectively. The primary objective of this work is to formulate an insecticide phytocoil from neem materials. The formulated insecticide phytocoil from both oil and neem leaves can be used as substitute to synthetic insecticides. Examining the repelling ability of the phytocoil confirms its ability to deter mosquitoes for up to 4 hrs in a small toilet room. Packaging as well as the improvement of the methodology of its mass production is suggested to enhance its looks and shape it to acceptable standard